The pragmatic MBA for scientific and technical executives - Liang, Bertrand C. (Academic Press, 2013)
This primer enables professionals with technical expertise to collaborate with their business-side colleagues. Emphasizing brevity and clarity, it gives technical staff answers to their most pressing questions about economics, finance, marketing, strategic decision-making, accounting, management, and related subjects. It does not offer condensed 1st year MBA courses; instead, it presents streamlined concepts and insights that are easy enough to be accessible and challenging enough to hold one's interest. Its examples from pharma, IT, aircraft/navigation, and other industries highlight problems that technical professionals face daily. Written by "one of them," its credibility makes it more useful than Internet resources. Because it concentrates on pragmatic (as opposed to academic) approaches to business, it empowers technical staff to stay with the conversation--and take it to a higher level. Bertrand C. Liang, MD, PhD, MBA, is Managing Director of LCC Ventures and Executive Director of Pfenex, Inc. He is trained in molecular biology and genetics (PhD) and is a clinician (MD) with subspecialty training in neurology and oncology, and serves as a Visiting University Professor at Liaoning He University, Shenyang, China. Creates frameworks and builds concepts enabling technical staff to work with their business colleaguesDelivers content for pragmatic, immediate use, not condensed presentations of subjects from first year MBA curriculumExtends readers' grasp by posting additional resources at a freely-available website